Urban Sustainability Engineering: Design of a Rainwater Harvesting and Automated Irrigation System in a Community Garden - Nascimento, Ana Paula Branco do; Araújo , Rafael Silva de; Rocha, Thais Reis; Serafini, Ramoel (National Journal of City Management, 2026)
Objective – To design and implement a rainwater harvesting and irrigation automation system for food plant beds located in a community garden under an impermeable roof, reducing dependence on manual irrigation by volunteers and promoting sustainable water management. Methodology – This applied research, with an exploratory and experimental approach, included bibliographic and technical surveys on rainwater harvesting systems, irrigation automation, and sustainable urban agriculture. The project was developed through field measurements, hydraulic efficiency tests, and component adjustments, resulting in the installation of an automated irrigation system at Horta das Flores, located in the eastern region of São Paulo, Brazil. Relevance – The proposal integrates engineering, automation, and urban sustainability by applying accessible technology for rainwater reuse in a community and educational context. The studied garden functions as a pedagogical space, hosting events and educational activities on sustainability and the Sustainable Development Goals (SDGs), thus reinforcing the connection with the 2030 Agenda. It stands out for its replicability in small-scale urban gardens and its direct contribution to SDGs 2, 3, 4, 6, 11, 12, and 13. Results – The system proved technically and operationally feasible, ensuring regular water supply and reducing manual effort. Field evaluation enabled hydraulic improvements and automation adjustments, confirming the potential for optimizing water use and increasing efficiency in urban water management. Methodological contributions – The study broadens the debate on the application of sustainable technologies and automated systems in urban agriculture, providing technical and academic foundations for replication in other urban contexts. Social and environmental contributions – The project strengthened the integration between university and community, encouraging environmental education, social participation, and shared water governance. By promoting rational water use and local food production, it reinforces the importance of integrated solutions for sustainable cities.